PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR DAN KETRAMPILAN BERPIKIR KRITIS MATERI GEOMETRI PADA SISWA SMP - Sofia Sa'o; Agustina Mei; Finsensius Yesekiel Naja (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This study aims to improve critical thinking skills and student learning outcomes of geometry material by applying problem-based learning. This research is a type of classroom action research with the John Elliot model with four stages, namely planning, implementation, observation and reflection, which is carried out in two cycles. The data obtained were obtained from instruments in the form of an assessment rubric for critical thinking skills and tests to determine student learning outcomes on geometry material. The subjects in this study were class VII students of SMP Rewarangga Ende, totalling 20 people. Technical analysis of the data using a comparative descriptive technique between cycles. The results showed that: (1) there was an increase in students' critical thinking skills from the initial conditions, cycle 1, and cycle 2. In the initial condition the level of critical thinking skills in the critical category was only 43%, in cycle 1 76%, and in cycle 2 increased to 97%; (2) student learning outcomes of geometry material also increased. In the initial condition, only 42% of students experienced completeness, in cycle 1 it increased to 51% of students who completed, and in cycle 2 it increased to 68%.